The Borders in All of Us: New Approaches to Global Diasporic Societies - Little, William A.; Williams, Selase W.; Vásquez, Irene; Furusa, Munashe; Park, Jung-Sun (New World African Press, 2006)
Keywords: Emigration and immigration; History; dept.aa

Collected Articles of Selase W. Williams. - Williams, Selase W. (2005)
Keywords: African Americans; Languages; English language; United States; Creole dialects; Variation; dept.aa; faculty_collection

Leadership as Place - Beatty, Ellen; Page, Robert (Leadership in Place: How Academic Professionals Can Find Their Leadership Voice, 2007)
Keywords: Administration; Universities and colleges; Faculty; Educational leadership; United States; Universities and colleges; dept.aa; dept.mgt; faculty_collection

Mass exhumation and deposition of Mulinia lateralis (Bivalvia: Mactridae) on an intertidal beach, St. Catherines Island, Georgia, USA - Cleveland, C.M.; Prezant, Robert; Rollins, Harold; Toll, R.; Wylie, J. (Veliger -Berkeley-, 2002)
Episodic events which affect populations of marine invertebrate species are rarely documented. We report the catastrophic mass exhumation and deposition of a large aggregation of adult bivalves (Mulinia lateralis [Say, 1822]) to a suboptimal habitat on a sandy intertidal beach of St. Catherines Island, Georgia, USA. The displaced population impacted a large area (7000 m2) of the beach and consisted of similar-sized clams (∼ 13 mm mean shell length). We suggest that the exhumation could have been a result of storm-induced shear stress, an hypoxic event, or other environmental stress on the individuals. Events of this type could have important implications for population dynamics and cohort distribution, fisheries predictions and harvests, and interpretation of fossil assemblages.
Keywords: dept.aa; ⛔ No DOI found

Mollusca of Assateague Island, Maryland and Virginia: Additions to the fauna, range extensions, and gigantism - Prezant, Robert; III, C.L.; Chapman, E.J. (Veliger, 2002)
Collections of 108 species of marine and estuarine mollusks from and around Assateague Island, Maryland and Virginia, from 1991 to 1996, vary from and extend the known species lists generated by three previously published collections over the past 100 years. Extensive sampling, including benthic grabs, trawls, and hand collecting, has added 54 species of mollusks (20 bivalves, 31 gastropods, one polyplacophoran, and two cephalopods) to the 1914 list of Henderson & Bartsch and 46 (19 bivalves, 26 gastropods and one cephalopod) to that of Counts & Bashore from 1991. Homer et al. in 1997 provided a mollusk survey of Maryland coast bays and listed 73 molluscan species (including 10 species recorded as shells only and eight as taxonomic uncertainties). To the latter we have added 51 molluscan taxa they did not find (19 bivalves, 29 gastropods, one polyplacophoran, and two cephalopods). All collections represent a total described malacofauna of this region of 146 shallow-water species excluding undescribed or non-described taxa in earlier papers. Within the populations of some of the species collected were a few exceptionally large individuals, adding to previous records of unusually large specimens of mollusks from this region of the Atlantic coast. Additionally, some species of mollusks (Tectura testudinalis, Eupleura semisulcata [Gastropoda], Tridonta borealis [Bivalvia]) and some non-mollusks (the ascidian Ecteinascidia turbinata and a confirmation of an extension of the anthozoan Peachia parasitica) have been found in the waters surrounding Assateague, well outside of their previously reported geographic ranges. The results of the present study suggest the need for a re-evaluation of possible environmental shifts that could have taken place since the collections of the early 1900s and have elsewhere been implicated in the change of malacofauna of Assateague Island since that time. Additionally, range extensions reported could reflect a subtle geographic transition zone, newly introduced species, or, most likely, an understudied coastal area.
Keywords: dept.aa; ⛔ No DOI found

Marine Macroinvertebrate Diversity of St. Catherines Island, Georgia - Prezant, Robert; TOLL, RONALD; Rollins, Harold; CHAPMAN, ERIC (American Museum Novitates, 2002)
St. Catherines Island is one of several barrier islands lining the coast of Georgia, USA. This island is among the least recently anthropogenically impacted of the Georgia Sea Islands, but had not previously been examined in detail for coastal invertebrate macrofauna. From 1992 through late 1998 a coastal survey was conducted that examined the diverse marine invertebrate fauna of St. Catherines Island. Salt marshes, sand flats, mid- to low-energy sand beaches, beach wood debris, tidal creeks, shallow benthos, and artificial hard substrata (including docks) were qualitatively sampled for macroinvertebrates. Over 340 species were identified. Crustaceans composed close to 40% (14% amphipods; 15% decapods), polychaetes 17.5%, and molluscs about 25% of all species recovered. These results are compared to the few other relevant studies from the United States mid-Atlantic Coast.
Keywords: dept.aa

A novel method for locating tagged infaunal bivalves: Submersible pulse technology metal detectors - Toll, R.B.; Prezant, Robert; Rollins, Harold (Journal of Shellfish Research, 2002)
Hardelams, Mercenaria mercenaria (Linne, 1758), tagged with brass washers attached to the outer shell surface and replanted into their natural habitat, were located remotely through the use of a commercially available, fully submersible, pulse technology metal detector. The ability to remotely locate tagged, replanted clams can increase the speed and efficiency of field operations associated with studies of clam population dynamics. Also, this methodology can reduce localized disturbances to the habitat that routinely accompany extensive hand probing to relocate experimental clams in traditional tag and recapture based studies.
Keywords: dept.aa; ⛔ No DOI found

Freshwater Molluscs of the United States Military Academy Drainages (West Point, NY) and Comparative Regional Biodiversity of Gastropods - Prezant, Robert S.; Chapman, Eric J. (Northeastern Naturalist, 2004)
Thirty-four species of molluscs have been found in the drainage systems of the United States Military Academy at West Point, NY. A few rare species were found as well as a single specimen of a presumed new gastropod taxon. Only two species of unionids, Pyganodon cataracta and Elliptio complanata, were found within the drainages. The largest drainage system, Popolopen Brook, contained the highest diversity of molluscs. Species redundancy between drainages aligned well as a function of the extent of lentic and lotic habitats with brooks and streams having a Bray-Curtis similarity index of ≈ 64.0 when compared to lakes and ponds. On the other hand, a number of species collected were found in only a single drainage. Total drainage area did not correspond well with diversity unless determined as total predicted usable habitat. Thus the drainages with the greatest number of discernible lakes, ponds, streams, and creeks, also had the highest molluscan diversity. On the whole, molluscan diversity of these drainages compared favorably to those of other regional New York sites, but relative abundance or population densities varied, with variations reflecting survey effort, time or season of collections, and incorporation of historic museum collections.
Keywords: dept.aa; peer-reviewed

Byssus-attachment by infaunal clams: Seagrass-nestling Venerupis in Esperance Bay, Western Australia (Bivalvia: Veneridae). - Bieler, Rüdiger; Mikkelsen, Paula; Prezant, Robert (2005)
Venerupis galactites (Lamarck, 1818), an endemic Australian infauna! venerid clam, is morphologically/ anatomically described based on specimens collected in shallow-water Posidonia australis seagrass beds in Esperance Bay, Western Australia. The species lives in high densities (1 ,300/m2) in 2-4 cm sediment depth, byssally attached to the seagrass rhizome mats. Notable features of its anatomy include elongated siphons that are united nearly to the tip, expansive plicated gills, and a prominent byssal groove on the posteroventral foot. The byssal gland in histological sections is irregularly ovoid and cupulate, with a narrow lumen; the microfibrillar ribbon-like byssus forms a single thick proximal stalk that divides distally into 2- 3 branches. Each branch can have numerous periodic, flat and parallel side-branches that extend from one side of the primary byssal thread and terminate in attachment plaques. The form of the byssus is reflected in the byssal duct, which has an infolded secretory epithelium that forms or molds the side branches. Byssal attachment by adult clams is discussed for the largely free-living and infauna! family Veneridae, a group in which neotenous retention of this postlarval feature was thought to be restricted to intertidal rock nestlers. Rather than representing a simple retention of neotenous features, the elaborate byssal apparatus of V galactites is clearly derived. The parallel side branches seen along a single side of the primary byssal threads could reflect an adaptive feature for secure adhesion in an infaunal life mode nestled along relatively narrow, cylindrical rhizomes.
Keywords: dept.aa

Can we save the urban river? - Prezant, Robert (Urban Dimensions of Environmental Change: Science, Exposures, Policies and Technologies, 2006)
Keywords: dept.aa

In utero predator-induced responses in the viviparid snail Bellamya chinensis - Prezant, R.S.; Chapman, E.J.; McDougall, A. (Canadian Journal of Zoology, 2006)
Keywords: dept.aa

Human exploitation of the quahog Mercenaria mercenaria in Eastern North America: Historical patterns and controls - Rollins, Harold; Prezant, Robert; Toll, R. (Archaeological Reports, 2008)
Keywords: dept.aa; ⛔ No DOI found

Population study of laternula truncata (bivalvia: anomalodesmata: laternulidae) in the mangrove sand flat of kungkrabaen bay, thailand, with notes on laternula cf. corrugata - Prezant, R.; Sutcharit, C.; Chalermwat, K.; Duangdee, Teerapong (Proceedings of the International Marine Bivalve Workshop, Chanthaburi, Thailand, 2008)
Overall benthic macroinvertebrate biodiversity, along with laternulid density, was higher closer to mangroves but relative infaunal invertebrate dominance increased along a transect that transcended a hummock closer to the mangrove forest, across an open sand fl at, and terminated in another isolated humMock farther from the fringing forest. A population of the anomalodesmatan bivalve Laternula truncata (Lamarck, 1818) was examined in a mangrove sand fl at in Kungkrabaen Bay, Thailand, to determine population size, cohort distribution, and basic relationships with sediment and infaunal macroinvertebrate biodiversity. Relatively high densities of L. truncata were found in muddy sands, often deeply buried in or close to tangled rootlet mats of the mangrove trees Avicennia alba Blume, 1827, and A. marina (Forsskal) Vierhapper, 1907, along isolated mangrove hummocks. They were less common in open areas of the mangrove fl at. This population of L. truncata was relatively evenly distributed across size classes, minus the smallest sizes, suggesting continuous recruitment with a possible loss of recent recruits or recruitment. Overall benthic macroinvertebrate biodiversity, along with laternulid density, was higher closer to mangroves but relative infaunal invertebrate dominance increased along a transect that transcended a hummock closer to the mangrove forest, across an open sand fl at, and terminated in another isolated hummock farther from the fringing forest. A nearby population of L. cf. corrugata (Reeve, 1863) inhabited a distinctly different habitat. Laternula cf. corrugata was shallowly buried and dwelt in the mangrove forest proper among different species of mangroves and in sandier sediments. Behavioural observations of both laternulids indicated that both were capable of reburying, with smaller specimens more rapidly, albeit still slowly, succeeding in full re-entry into the sediment. Larger specimens of L. truncata were incapable of reburial. Morphological, ecological, and behavioural distinctions between L. truncata and L. cf. corrugata are considered in light of their habitat differences, confusion within laternulid systematics, and diffi culty in resolving the taxonomy of the latter species.
Keywords: dept.aa; ⛔ No DOI found

Immigrant act - Crawford, I. (JAC: A Journal of Composition Theory, 2006)
Keywords: dept.aa; ⛔ No DOI found

The use of hi fidelity simulation to enhance nursing students' therapeutic communication skills - Sleeper, J.A.; Thompson, C. (International Journal of Nursing Education Scholarship, 2008)
Nursing students entering psychiatric settings for clinical practice need a solid foundation of therapeutic communication skills. This article presents an innovative strategy for nursing students to practice therapeutic communication skills with psychiatric patients by using hi fidelity simulation with Laerdal SimMan. Using the SimMan vocal function enabled nurse educators to develop communication algorithms that allowed students to interact with SimMan as they would with psychiatric patients. The SimMan algorithms can be designed to mimic many scenarios typically found in psychiatric settings. Nursing students can use this technology to take the therapeutic communication skills they have learned in the classroom and practice them in a safe laboratory environment before entering actual psychiatric settings. The ability of students to practice communication skills prior to entering psychiatric settings can promote effective therapeutic communication skills and decrease student anxiety. Copyright ©2008 The Berkeley Electronic Press. All rights reserved.
Keywords: Communication; Psychiatric patients; SimMan; Teaching strategies; dept.aa

The role of precollege data in assessing and understanding student engagement in college - Cole, James S.; Kennedy, Marianne; Ben-Avie, Michael (New Directions for Institutional Research, 2009)
Keywords: dept.aa